Panorama of nursing distance education in Brazil - Rojo, Priscila Tagliaferro; Vieira, Sheila de Souza; Zem-Mascarenhas, Silvia Helena; Sandor, Elisane Regina; Vieira, Carla Roberta Sola de Paula (Revista da Escola de Enfermagem da USP, 2011)
The development of distance education is associated with the popularization and democratization of the accessibility to information and communication technologies. Nursing has been using this modality of education in both undergraduate and graduate courses, which has provided knowledge about other technologies, an easier accessibility, flexibility of time and space, and reduced costs. The objective of this study is map the national higher education distance nursing courses. This exploratory, descriptive study was developed by visiting governmental, non-governmental and institutional websites. Two undergraduate and nine graduate courses in nursing were found, which is considered to be a low number, considering that distance education is an appropriate pedagogical tool that permits to prepare a large number of nurses who are geographically dispersed and who do not have access to the conventional educational processes.